Efektivitas Penggunaan Game Edukasi Digital Interaktif Wordwall Terhadap Peningkatan Minat dan Hasil Belajar Matematika di Kelas 4 SDN 1 Sampora dan Kelas 4 SDN 3 Sampora - Fitri, Lina Karlina; Manan, Nanan Abdul (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The aim of this research is to determine the effect of digital media usage on the interest and learning outcomes of fourth-grade students. This research employs a quantitative approach with a Quasi-Experimental design. Data collection techniques were conducted through observation, interviews, tests, questionnaires, and documentation. The research instruments were tested for validity and reliability, while the data were analyzed using normality tests, homogeneity tests, hypothesis tests, and non-parametric tests. The research subjects involved 25 fourth-grade students from SDN 1 Sampora and 25 fourth-grade students from SDN 3 Sampora. The results indicate that the use of digital media has a positive effect on students' learning interest. Students appear more enthusiastic in participating in the lessons, active in discussions, and show an improvement in classroom participation. In addition, the students' learning test results also showed a significant improvement compared to learning using conventional media. The hypothesis test proved that there is a significant difference in average learning outcomes between the experimental class and the control class, indicating the effectiveness of digital media in enhancing the understanding of flat shape concepts. Thus, the use of digital media can be considered a relevant alternative to improve the quality of mathematics learning in elementary schools, both in terms of interest and student learning outcomes.